A Case Study: Diagnosis of Intestinal Myiasis Maggot in a Mature Male in Baghdad - Al-Dujaily, Khitam; Abd- Ullah, Iqbal; Jasim, Raya; Abd-Hameed, Entisar (Iraqi Journal of Science, 2025)
Myiasis is abnormal case of man infection due to either ovulating flies in the wounds which called cutaneous myiasis or due to ingestion of eggs of the flies accidentally with food which causes the gastric or intestinal myiasis .We report here a case of myiasis in a mature male (60 years old) sent by a private clinic in Baghdad to parasitological section /Central Public Health Laboratories (CPHL) /Baghdad and by the help of Museum of Natural History, it diagnosed as intestinal myiasis.